Pro ASP.NET 2.0 in VB 2005 - Moroney, Laurence (Apress, 2012)
In this book, you’ll learn everything you need to master ASP.NET 2.0. If you’ve programmed with a previous version of ASP.NET, you’ll sail through the basics and quickly begin learning about the exciting new features in version 2.0. If you’ve never programmed with ASP.NET, you’ll find that this book provides a well-paced tour that leads you through all the fundamentals and gives you a backstage pass so you can see how the ASP.NET internals really work.U